Impact of Social Media on Entrepreneurial Marketing and Communications - Bin Tehsin, Ahmad (2018)
The use of social media is at a rise and it is now becoming a part of people’s everyday life. This increased use has enforced the companies and businesses to market their products over social media to achieve their marketing and firm objectives. While talking about the businesses, entrepreneurship is increasing day by day and entrepreneurs also act as a marketer of their companies. This article explores how these entrepreneurs use different tools to communicate their ideas and products in the market especially by social media. The interviews of entrepreneurs of an incubation center based in the University of Nottingham are conducted in the study which gave the opportunity to explore their marketing strategies at initial and growth stage of businesses. The article does not only state the role of social media only but also other traditional marketing tools which help entrepreneurs to effectively market their startups. The research question “Impact of social media on entrepreneurial marketing and communication” is explored and answered using different qualitative methods of data collection and analysis. Lastly, this article does not only add up the literature, but it can also be used practically by upcoming entrepreneurs to learn about marketing strategies and tools to be used for their startups.